Ballistic-penetration resistance and flexural-stiffness optimization of a nacre-mimetic, B4C-reinforced, polyurea-matrix composite armor - Grujicic, Mica; Snipes, Jennifer; Ramaswami, S (International journal of structural integrity, 2017)
Purpose The purpose of this paper is to model a nacre-like composite material, consisting of tablets and polyurea tablet/tablet interfaces, B4C. This composite material is being considered in the construction of the so-called backing-plate, a layer within a multi-functional/multi-layer armor system. Design/methodology/approach Considering the basic functions of the backing-plate (i.e. to provide structural support for the ceramic-strike-face and to stop a high-velocity projectile and the accompanying fragments) in such an armor system, the composite-material architecture is optimized with respect to simultaneously achieving high flexural stiffness and high ballistic-penetration resistance. Flexural stiffness and penetration resistance, for a given architecture of the nacre-like composite material, are assessed using a series of transient non-linear dynamics finite-element analyses. The suitability of the optimized composite material for use in backing-plate applications is then evaluated by comparing its performance against that of the rolled homogeneous armor (RHA), a common choice for the backing-plate material. Findings The results obtained established: a trade-off between the requirements for a high flexural stiffness and a high ballistic-penetration resistance in the nacre-like composite material; and overall superiority of the subject composite material over the RHA when used in the construction of the backing-plate within multi-functional/multi-layer armor systems. Originality/value This study extends the authors previous research on nacre-mimetic armor to optimize the architecture of the armor with respect to its flexural stiffness and ballistic-penetration resistance, so that these properties could be increased over the levels attained in the current choice (RHA) for the backing layer of multi-functional/multi-layer armor.